The Influence of Self Efficacy, Procrastination Academic and Learning Environment on Academic Fraud Behavior of Student Department of Accounting and Finance Institution of SMK Negeri 1 Yogyakarta - Siregar, Merinda Noorma Novida; Kusmiyati, Iin (Jurnal Pendidikan Akuntansi (JPAK), 2024)
The objectives of this study are to: (1) identify the influence of self-efficacy on academic dishonesty among accounting students at SMK Negeri 1 Yogyakarta; (2) identify the influence of academic procrastination on academic dishonesty among accounting students at SMK Negeri 1 Yogyakarta; and (3) identify the influence of the learning environment on academic dishonesty among accounting students at SMK Negeri 1 Yogyakarta. The population of this study consisted of 202 students from classes X, XII, and XII at SMK Negeri 1 Yogyakarta who were majoring in accounting. 36 students in class X AKKL 1 Accounting and Finance Expertise Program at SMK Negeri 1 Yogyakarta participated in instrument trials. The linearity test, the multicollinearity test, and the heteroscedasticity test were the prerequisite tests in this study. The analysis technique used in this research is simple regression analysis for the first, second and third hypotheses. The results of this study indicate that: 1) There is a negative effect of Self Efficacy on Academic Fraud Behavior of Students majoring in Accounting at SMK Negeri 1 Yogyakarta with a correlation coefficient of -0,286 and a coefficient of determination of 0,082; 2) There is a positive effect of Academic Procrastination on Academic Fraud Behavior of Students majoring in Accounting at SMK Negeri 1 Yogyakarta with a correlation coefficient of of 0,186 and a coefficient of determination of of 0,135; 3) There is a negative effect of the Learning Environment on the Academic Fraud Behavior of Students majoring in Accounting at SMK Negeri 1 Yogyakarta with a correlation coefficient of -0,375 and a coefficient of determination of of 0,145.